IQ challenge - Cameron, Joe; Illustrated (Arcturus Publishing Ltd Australia, 2000)
"IQ Challenge" is a puzzle and brain teaser book designed to test and improve problem-solving, logical reasoning, and analytical thinking skills through a variety of challenging exercises.